Broadband optoelectronic synaptic devices based on silicon nanocrystals for neuromorphic computing. (October 2018) - Tan, Hua; Ni, Zhenyi; Peng, Wenbing; Du, Sichao; Liu, Xiangkai; Zhao, Shuangyi; Li, Wei; Ye, Zhi; Xu, Mingsheng; Xu, Yang; Pi, Xiaodong; Yang, Deren
Abstract: Optically stimulated synaptic devices are critical to the development of neuromorphic computing with broad bandwidth and efficient interconnect. Although a few interesting materials have been employed to fabricate optically stimulated synaptic devices, the use of silicon (Si) that is the material of choice for very large-scale integration circuits in the conventional von Neumann computing has not been explored for optically stimulated synaptic devices. Here we take advantage of one of the most important nanostructures of Si — Si nanocrystals (NCs) to make synaptic devices, which can be effectively stimulated by light in the unprecedented broad spectral region from the ultraviolet to near-infrared, approaching the wavelength of ∼ 2 µm. These optically stimulated Si-NC-based synaptic devices demonstrate a series of important synaptic functionalities, well mimicking biological synapses. The plasticity of Si-NC-based synaptic devices originates from the dynamic trapping and release of photogenerated carriers at defects such as dangling bonds at the NC surface. The current facile use of Si NCs in broadband optoelectronic synaptic devices with low energy consumption has important implication for the large-scale deployment of Si in the emerging neuromorphic computing. Graphical abstract: Silicon nanocrystals (Si NCs) are used to fabricate optoelectronic synaptic devices whose energy consumption may be rather low. Essential synaptic functionalities have been realized in these devices by using broadband light to stimulate them. fx1 Highlights: Silicon nanocrystals (Si NCs) are used to fabricate optoelectronic synaptic devices. Main functionalities of biological synapses are emulated by using broadband light. The operation is basically governed by the electronic and optical behavior of Si NCs.